Cognitive Behavioural Therapy to Optimize Post-Operative Recovery (COPE): a randomized controlled feasibility trial in extremity fracture patients - Kyle Gouveia; Sheila Sprague; Jodi L. Gallant; Sarah MacRae; Gina Del Fabbro; Sofia Bzovsky; Paula McKay; Herman Johal; Jason W. Busse; on behalf of the COPE Investigators (Pilot and Feasibility Studies)
Abstract Background Outcomes following surgery to operatively manage extremity fractures are variable, and up to two-thirds of patients report chronic post-surgical pain. Preliminary evidence suggests that psychotherapy directed at improving coping skills and reducing somatic vigilance may improve outcomes among fracture patients. The objective of this pilot study was to test the feasibility and acceptability of a randomized controlled trial comparing an online cognitive behavioural therapy (CBT) program versus usual care in patients with an operatively managed open or closed extremity fracture. Methods We conducted a single-centre internal pilot study over a 10-month period in patients with at least one operatively managed open or closed fracture of the appendicular skeleton. Participants were randomized to an online CBT program or usual care and followed for 12 months. The goals of our pilot study were to determine an acceptable rate of recruitment, the degree to which participants randomized to CBT were compliant with treatment, the site investigator’s ability to adhere to study protocol and data collection procedures, and our ability to achieve high follow-up rates. Feasibility criteria were evaluated using a graded “traffic light” approach, in which “green light” indicates moving forward with the definitive trial, “yellow light” indicates proceeding with modifications to the protocol and trial procedures, and “red light” indicates a definitive trial is not feasible without significant protocol and trial procedure modifications. Results We enrolled 94 participants over 10 months, which resulted in a “yellow light” for recruitment. Participant compliance with completion of the online CBT program received a “yellow light”, with 60% of participants who were randomized to CBT completing all seven modules. However, 40% of participants in the CBT-arm withdrew from the program, resulting in a “red light”. Adherence with the study protocol activities at baseline was relatively high (88%) which resulted in a “yellow light”. Follow-up was 85% (80 of 94) at 12 months, resulting in a “yellow light”. Conclusions These results suggest feasibility of a definitive, multi-centre trial to compare CBT versus usual care in the management of persistent post-operative pain in fracture patients despite the pilot phase identifying some challenges with enrollment timelines, compliance with the CBT program, and participant follow-up. For the definitive trial, we will expand participant recruitment to additional centres and implement strategies to optimize participant engagement and compliance with the CBT program and follow-up. Trial registration ClincialTrials.gov (NCT04274530). Registered February 18, 2020, https://classic.clinicaltrials.gov/ct2/show/NCT04274530 .